IMPROVEMENT OF THE ALGORITHM FOR INTRAOPERATIVE DIAGNOSTICS OF BREAST CANCER METASTASIS USING SENTINEL LYMPH NODE STAINING - Nikitenko, R.P.; Kosovan, V.M.; Vorotyntseva, K.O.; Koichev, E.A.; Degtyarenko, S.P.; Kvasha, O.M.; Likhachov, V.K. (World of Medicine and Biology, 2023)
Lymphatic metastasis is one of the most important causes of local BC recurrence and an unfavourable prognosis factor. With the beginning of application in the surgical practice of staining sentinel lymph nodes using modern dyes (Patent Blue, ICG), the approach to determining the extent of surgical intervention has changed radically Performing the staining of sentinel lymph nodes in breast tumours allows for reducing the trauma of surgical intervention as much as possible (due to the refusal of axillary lymph node dissection), as a result of which the number of postoperative complications is minimised. The purpose of the study was to improve the algorithm for intraoperative detection of sentinel lymph nodes in patients with breast cancer. Between 2016 and 2021, 200 patients with T1-T3N0M0 breast cancer were operated on at the Odesa Regional Clinical Hospital using two dyes: Patent Blue and ICG. The proposed algorithm for diagnosis and treatment of breast cancer allows most cases to abandon traumatic operations in favour of organ-preserving operations with biopsy of sentinel lymph nodes.
Keywords: breast cancer; sentinel lymph nodes; intraoperative staining of lymph nodes; biopsy